2010
DOI: 10.1227/01.neu.0000366111.08024.26
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived Growth Factor-Induced Severe and Chronic Vasoconstriction of Cerebral Arteries

Abstract: PDGF-BB, a growth factor synthesized in the subarachnoid space after SAH, can cause severe and long-lasting vasoconstriction. Significant prevention and resolution of vasospasm can be achieved by the PDGF-BB antagonist trapidil. We propose that excessive production of PDGF-BB, essentially aiming to repair injured arteries, causes cerebral vasospasm. Although the half-life of trapidil in serum may be shorter than that of PDGFG-BB-derived spasmogenic signaling, trapidil is a candidate drug for constructing a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 46 publications
0
17
1
Order By: Relevance
“…However, Zhang et al [72,77] found that recombinant PDGF-BB (5–10 µg) causes delayed contraction of cerebral arteries in a dose-dependent manner in vivo (fig. 3b).…”
Section: Cisternal Injection Of Pdgf-bb Causes Prolonged Contraction mentioning
confidence: 99%
See 4 more Smart Citations
“…However, Zhang et al [72,77] found that recombinant PDGF-BB (5–10 µg) causes delayed contraction of cerebral arteries in a dose-dependent manner in vivo (fig. 3b).…”
Section: Cisternal Injection Of Pdgf-bb Causes Prolonged Contraction mentioning
confidence: 99%
“…Zhang et al [77] examined the therapeutic potential of trapidil (5–30 mg/kg/day) using the rabbit SAH model [77,79]. Either starting 1 h after the induction of SAH (on day 0) and continuing for 47 h, or starting after the development of vasospasm (on day 2) and continuing for 30 min (3 mg/kg/h), caliber alterations of the basilar artery were analyzed on angiography.…”
Section: An Antagonist Of Pdgf-bb Function Suppresses the Developmentmentioning
confidence: 99%
See 3 more Smart Citations